The government of Indonesia’s smart city development: Fiscal capacity, cognitive models in decision making, excessive caution about future accrual of benefits, and null regulatory leadership - Bastian, Indra; Effendi, Ruslan; Susanto, Efa Agus; Unggara, Ilham; Sumiyana, Sumiyana (Frontiers in Built Environment, 2022)
This article investigates the lack of certainty regarding the success of smart city development in the Government of Indonesia’s regions. The authors suspect that developing smart cities in each region ran independently and nationally, without a unifying strand of knowledge and information system leadership models. Based on these statuses and circumstances, this research examines these phenomena with two critical perspectives: the cognitive model of double-loop learning of smart city development and a dexterous strategy in terms of political economy. Consequently, this study finds that the regions developing a smart city act according to the statuses: working with only fiscal budget readiness, cognitive models in the decisions to create future works, excessive caution about accruing potential future benefits, and null regulatory leadership in terms of guidelines. Thus, this study concludes that regions develop smart cities in their self-imagination without profound directional boundaries.